THE IMPACT OF DIFFERENTIATION STRATEGY AND PRODUCT INNOVATION ON COMPETITIVE ADVANTAGE IN THE ECO-FRIENDLY FASHION INDUSTRY - Lilis Sulastri; Iir Abdul Haris; Diva Nuraini Purnama; Rizky Indah Putri Christianto; Agung Muhamad Yoransah (UIN Sunan Gunung Djati Bandung, 2025)
The fashion industry today faces intense competition and growing consumer demand for products that are not only aesthetically appealing but also sustainable. This study aims to analyze the effect of differentiation strategy and product innovation on competitive advantage in eco-friendly fashion companies. A qualitative case study was conducted on Company X, a leading player in Indonesia’s sustainable fashion sector. Data were collected through in-depth interviews, field observations, and company documentation. The data were analyzed descriptively to identify best practices in implementing differentiation and product innovation strategies. The results indicate that the implementation of differentiation strategy, supported by product innovation, significantly enhances competitive advantage, particularly through product value-added, unique design, and eco-friendly brand image.